2004
DOI: 10.1249/01.mss.0000113479.98631.c4
|View full text |Cite
|
Sign up to set email alerts
|

Heritability in Neuromuscular Coordination: Implications for Motor Control Strategies

Abstract: In this study, heredity accounted for most of the existing differences in neuromuscular coordination in fast movements. This implies that movement strategies, which are organized in the CNS and control fast movements, are also strongly genetically dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 18 publications
0
16
0
4
Order By: Relevance
“…Analysis of heritability enabled to discover that body characteristics related to physical performance such as cardiovascular and respiratory variables, e.g., maximal oxygen uptake (VO2max), running velocity at the anaerobic threshold (VAT), cross-sectional surface area of muscles, neuromuscular coordination, as well as cardiovascular and respiratory systems’ variables have strong genetic background (An et al, 2003; Missitzi et al, 2004; Stanula et al, 2014; Stunkard et al, 1990). Rapid development of molecular methods enabling the research of the structure and sequence of the human genome, and the usage of the model based on association analysis of candidate genes in sports has become feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of heritability enabled to discover that body characteristics related to physical performance such as cardiovascular and respiratory variables, e.g., maximal oxygen uptake (VO2max), running velocity at the anaerobic threshold (VAT), cross-sectional surface area of muscles, neuromuscular coordination, as well as cardiovascular and respiratory systems’ variables have strong genetic background (An et al, 2003; Missitzi et al, 2004; Stanula et al, 2014; Stunkard et al, 1990). Rapid development of molecular methods enabling the research of the structure and sequence of the human genome, and the usage of the model based on association analysis of candidate genes in sports has become feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D seems to be involved on this type of activities. It is well documented that its levels are related with muscle strength [5], the proportion and the diameter of type II muscle fibers [16], and neuromuscular coordination [12], which are of paramount importance for explosive type human movements, such as sprints and jumps [17], [18], [19]. Moreover, the presence of vitamin D receptors (VDR) in the muscle cell appears to influence muscle strength.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this study along with afferent information, centrally generated motor command signals, which have been found to have a genetic basis (Missitzi et al. ), is likely to play a major role. Hence, any part of the system concerned with the generation of the force production task, collection or processing of afferent information or the generation of efferent signals may be genetically influenced.…”
Section: Discussionmentioning
confidence: 82%
“…A comparison of intrapair differences between MZ and DZ twins in neuromuscular coordination of fast movements, expressed either as movement accuracy or movement economy, demonstrated that heredity accounts for the major part (87%) of existing differences (Missitzi et al. ). The heritability estimate of motor control found in this study (0.68) was lower than that found previously relating to neuromuscular coordination measures, an observation that may be explained by the fact that different tasks challenge multiple sensory and motor capacities differently and are each subject to different heritability (J. Missitzi, A. Misitzi, N. Geladas, J. Classen, and V. Klissouras, unpubl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation